Analisis Kinerja Pegawai Dalam Meningkatkan Pelayanan Publik di Kantor Camat Woyla Barat Kabupaten Aceh Barat - Nurmasyitah, Nurmasyitah; Najamudin, Najamudin (Indonesian Journal Publisher, 2025)
This study aims to determine how employee performance is in improving public services at the Woyla Barat District Office, West Aceh Regency, and to identify supporting and inhibiting factors for this performance. The research method used is qualitative with a descriptive research type. Informants were selected using purposive sampling techniques based on certain criteria that are relevant to the study. Data collection was carried out through in-depth interviews, direct observation, and documentation to obtain a comprehensive picture of employee performance and the factors that influence it. The results of the study indicate that employee performance in providing public services is quite good, seen from indicators of service quality, quantity of work, punctuality, work effectiveness, independence, and employee commitment which show positive results. The main supporting factors for employee performance are the attitude of serving the community in a friendly and sincere manner according to conscience and the availability of adequate facilities and infrastructure so that the service process runs smoothly. However, there are obstacles that affect performance, namely internal factors in the form of lack of employee discipline and external factors such as incomplete data brought by the community and the impatient attitude of the community when receiving services. In conclusion, the performance of employees at the Woyla Barat District Office is quite good, but improvements need to be made, especially in increasing employee discipline and public patience so that public services can be more optimal and satisfy the community as a whole.